High-Torque-Density IPMSM Rotor Pole Geometry Adjustment for Smooth Torque - Ilya Petrov (IEEE Access, 2019)
High-torque-density electrical machines applied to traction operate at a varying torque and speed, and therefore, when minimizing the torque ripple, a wide variety of possible loads must be considered. Different loads need different current vectors, which affect the magnetic state of the machine. Thus, the torque ripple must be analyzed by using appropriate current vectors as it is proposed and described in this paper. The torque ripple values were estimated also for a skewed machine using a new method of torque ripple estimation of a skewed machine. The method is computationally less heavy and allows computing the torque ripple at all possible load points. Using the proposed method in the analysis of the machine parameters, the rotor pole geometry was adjusted to minimize the torque ripple without degradation of the other properties of the machine. Finally, the best machine performance was compared with the measured results.